Group Guidance to Increase Learning Motivation in Children in Wangkelang Village - Lailatul Chikmah; Liu Amanah; Sevira Putri Solikha; Titah Iffahaini Patrista; Via Rizquna; Ma’rifatun Fauzah; Hendri Hermawan Adinugraha (Yayasan Adra Karima Hubbi, 2024)
Education is a process of self-development both individually and in groups. The level of public education participation is a measure of intelligence and progress of a country against other countries. School is a means of obtaining education, but because of the large number of students in one class, the teacher cannot guide one by one. This study aims to provide tutoring for elementary school students in Wangkelang Village. The method used is Community Service carried out by a community service team. Study groups are conducted by teaching students about literacy, numeracy and conducting socialization to increase public education awareness. After receiving study group guidance and outreach to increase educational awareness from the service team, students understand more about the importance of educational awareness and better understand literacy and numeracy materials in their learning. It is hoped that the results of this research can become a reference for other service teams in increasing public education awareness.